Liver fibrosis, insulin resistance and cardiovascular risk scores in obese and non-obese patients with non-alcoholic fatty liver disease - Dooshan, Arghavan; Forootan, Mojgan; Pirsalehi, Ali; Pourhoseingholi, Mohamad Amin; Hatami, Behzad (Novelty in Biomedicine, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease. Obese children and adolescents, particularly those with metabolic syndrome (MetS), commonly report NAFLD, which can lead to various other problems and diseases. There are different opinions on how the liver fibrosis score, insulin resistance indices, and risk of cardiovascular disease are related in people with NAFLD who have different body mass index (BMI) levels. This study aimed to investigate the relationship between liver fibrosis score, insulin resistance indices, and cardiovascular disease risk in patients with NAFLD, specifically focusing on two groups with normal and high BMI. Materials and Methods: This analytical cross-sectional study was conducted on patients with NAFLD referred to Taleghani Hospital (Tehran-Iran) between 2019 and 2020. Data such as age, gender, BMI, height, weight, blood sugar level, hemoglobin A1C level, lipid profile, liver fibrosis level, insulin resistance level, liver aminotransferases level, Framingham risk score, and presence of MetS were evaluated. The significance level was considered less than 0.05. Results: We evaluated 140 patients, 14 of whom had normal BMI, and the rest had high BMI. There was a significant relationship between the homeostatic model assessment for insulin resistance (HOMA-IR) index and the liver fibrosis score. For a one-unit increase in the liver fibrosis score, the HOMA-IR score increased by 0.287 times (P-value=0.001). There was a significant relationship between MetS and the risk of cardiovascular diseases based on the Framingham risk score and liver fibrosis (P-values<0.05). Conclusion: High BMI levels can increase the incidence of NAFLD, Framingham, and HOMA-IR indices.